KOSAKATA TANAMAN TRADISIONAL OBAT-OBATAN DALAM BAHASA BATAK TOBA KAJIAN ANTROPOLINGUISTIK - Tomson Sibarani (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Cultural studies and languages is Antropolinguistics study. Toba Batak language will change if the ecological support having changed anyway. Language Batak Toba area of research is in three sub-districts, Samosir, Laguboti, Porsea in Toba Samosir. The problem is, how the extinction of medicinal plants caused lexical sosial¬-cultural changes, the benefits of medicinal plants, community efforts to conserve medicinal plants in Toba Batak society? The goal is to describe the medicinal plants due to socio-cultural changes, the benefits of medicinal plants, medicinal plant conservation in Toba Batak society. This research was conducted using qualitative and quantitative. In analyzing the data in the study of medicinal plants vocabulary Batak Toba Match method is used. Use of drugs like this are usually relegated to the younger generation in a way put the drugs directly. The treatment process is usually done for generations, from parent to child by practicing or teaching the treatment process.